Fish and Floods: Implementation of the 2008 biological opinion on the National Flood Insurance Program in Washington State - Olson, Margaret (My University, 2013)
The National Flood Insurance Program (NFIP) is administered by the Federal Emergency Management Agency (FEMA) and provides flood insurance in communities who comply with minimum standards for building in floodplains. In 2008 a National Marine and Fisheries Service (NMFS) biological opinion concluded that the NFIP violated the 1973 Endangered Species Act (ESA) by jeopardizing threatened salmon and orca populations and their habitat in western Washington State. In the biological opinion, NMFS directed FEMA Region X to make specific changes that would stop additional harm to these species and their habitat in the 122 communities participating in the NFIP in western Washington. This research investigated the intentions and goals of the groups formulating the 2008 biological opinion, whether or not the implementation of the biological opinion had met those goals, and why. The research methods included review of official documents and correspondence, interviews with key figures in the creation and implementation of the biological opinion, and review of news articles and third party reports on the process. Case studies of two local communities were conducted to determine how different areas operating under different planning constraints received the biological opinion, what steps they took to implement it, and what effect it is having in their jurisdiction. This research was placed in a broader context of salmon restoration programs and floodplain management options in Washington State to illustrate the co-benefits of these policies. The success of the implementation process of Washington's 2008 biological opinion has national implications, since biological opinions on the NFIP are now being litigated or written in other states, including Oregon. As part of a review of the NFIP, FEMA is studying how best to incorporate the goals of the ESA into the NFIP.
Thesis (Master's)--University of Washington, 2013
Keywords: biological opinion; FEMA; implementation; NFIP; NMFS; salmon; Water resources management; Public policy; Environmental management; urban planning